Influence of Price and Product Quality on Customer Satisfaction at Chelsea Pet Studio Medan - Agustin, Kevin; Sutarno, Sutarno; Shara, Yuni; Akmal, Oktafiana (Cattleya Darmaya Fortuna, 2025)
Chelsea Pet Studio Medan has experienced a decrease in customer satisfaction as seen from several customers making complaints so that the influence on customer visits to Chelsea Pet Studio Medan has decreased due to price and product quality. The purpose to be achieved in this study is to determine the influence of Price and Product Quality on Customer Satisfaction at Chelsea Pet Studio Medan. The research method used is quantitative. The number of respondents was 200 customers and the number of samples was 64 customers with the sampling technique being simple random sampling. Price and product quality influence on Customer Satisfaction at Chelsea Pet Studio Medan. The magnitude of the coefficient of determination can be seen from the adjusted R Square value of 0.693, which means that price (X1) and product quality (X2) can explain customer satisfaction (Y) by 69.3% and the rest is influenced by other variables outside of this study.